Economic Conditions at Birth and Cardiovascular Disease Risk in Adulthood: Evidence from New Cohorts - Rob Alessie; Viola Angelini; Gerard J. van den Berg; Jochen O. Mierau; Laura Viluma (Institute of Labor Economics (IZA), 2017)
Most of the literature that exploits business cycle variation at birth to study long-run effects of economic conditions on health later in life is based on pre-1940 birth cohorts. They were born in times where social safety nets were largely absent and they grew up in societies with relatively low female labor force participation. We complement the evidence from this literature by exploiting post-1950 regional business cycle variations in the Netherlands to study effects on cardiovascular disease (CVD) risk in adulthood, by gender. We operationalize CVD risk by constructing the Systematic COronary Risk Evaluation (SCORE) index from an extensive set of biomarkers. The data are from a large cohort study covering socio-economic, biological and health data from over 75k individuals aged between 18 and 63. We conclude that women born in adverse economic conditions experience higher CVD risk.
Keywords: I10; I15; J11; 330; unemployment; health; recession; developmental origins; early-life conditions; long-run effects; biomarkers